Sensitive and selective electrochemical sensor for the detection of dopamine by using AuPd@Fe2O3 nanoparticles as catalyst - Mengjiao Dai; Qunyan Zhu; Dongxue Han; Li Niu; Zhenxin Wang (Advanced Sensor and Energy Materials, 2023)
The levels of dopamine (DA) in living organisms have strong effects on many biological processes and diseases, such as Parkinson's disease and Alzheimer's disease. Therefore, it has great significance for sensitive and selective detection of DA. Herein, the AuPd@Fe2O3 nanoparticles-based electrochemical (EC) sensor (AuPd@Fe2O3 NPs/GCE) is developed for chronoamperometric detection of DA with high sensitivity and good anti-interference ability through simple immobilization of AuPd@Fe2O3 nanoparticles on glassy carbon electrode (GCE) by Nafion. Under the application of oxidation potential, the AuPd@Fe2O3 NPs/GCE exhibits good electrocatalytic activity toward DA, which enables to linearly detect DA in the range of 10 nM–831.61 μM (R2 = 0.9983). The AuPd@Fe2O3 NPs/GCE also shows good selectivity and reproducibility for the detection of DA. Furthermore, the practicability of AuPd@Fe2O3 NPs/GCE has been demonstrated by detection of DA in dopamine hydrochloride injection and human serum.